1994
DOI: 10.1007/bf02276056
|View full text |Cite
|
Sign up to set email alerts
|

Detection of amplifiedChlamydia trachomatis DNA using a microtiter plate-based enzyme immunoassay

Abstract: A microtiter plate-based method to detect amplified DNA was developed. The method uses on biotin-labeled primer in the polymerase chain reaction (PCR) mixture. The labeled amplicon is bound to streptavidin-coated microtiter plates, denatured and hybridized to a digoxigenin-labeled probe. The specificity of the hybridization reaction was optimized by varying the temperature of the subsequent washing step and adding urea to the washing buffer. The digoxigenin label was detected using an enzyme immunoassay (EIA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…It is suggested that PCR assays especially detect more cases of low-grade, to cause more complaints of lower abdominal pain, and in men genotypes H and J produced more symptoms of dysuria and otherwise inapparent infections [34]. As a result, in our study some chlamydial infections remained undetected, especially urethral discharge.…”
Section: Symptoms and Signs On Examinationmentioning
confidence: 81%
See 2 more Smart Citations
“…It is suggested that PCR assays especially detect more cases of low-grade, to cause more complaints of lower abdominal pain, and in men genotypes H and J produced more symptoms of dysuria and otherwise inapparent infections [34]. As a result, in our study some chlamydial infections remained undetected, especially urethral discharge.…”
Section: Symptoms and Signs On Examinationmentioning
confidence: 81%
“…For the nested PCR, 1 mL was used in a second PCR C. trachomatis, as described previously [30]. One specimen was obtained by using the specially designed collection kit of using the primers NLI and NRI [34]. Both primer sets were designed to amplify all known serovars of C. trachomatis.…”
Section: Study Participants and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Urine and rectal swabs, which were collected in 2SP medium, were used for PCR testing. Genotyping of the gene encoding the major outer membrane protein (MOMP) was performed by nested PCR and RFLP analysis [6]. Serum specimens were collected and analyzed for the presence of specific IgA and IgG antibodies to C. trachomatis by peptide EIA (SeroCT; Savyon Diagnostics).…”
Section: Patient Populationmentioning
confidence: 99%
“…Chronic inflammation of the lymphatic vessels, progressive lymph edema, and sclerosing fibrosis may cause severe disfiguring conditions, such as genital elephantiasis and esthiomene [3,4]. Genotyping C. trachomatis by nested PCR and restriction fragment-length polymorphism (RFLP) allows a reliable diagnosis [5][6][7].…”
mentioning
confidence: 99%